2010
DOI: 10.1007/s00018-010-0571-8
|View full text |Cite
|
Sign up to set email alerts
|

Emerging knowledge of regulatory roles of d-amino acids in bacteria

Abstract: The d-enantiomers of amino acids have been thought to have relatively minor functions in biological processes. While l-amino acids clearly predominate in nature, d-amino acids are sometimes found in proteins that are not synthesized by ribosomes, and d-Ala and d-Glu are routinely found in the peptidoglycan cell wall of bacteria. Here, we review recent findings showing that d-amino acids have previously unappreciated regulatory roles in the bacterial kingdom. Many diverse bacterial phyla synthesize and release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
255
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(277 citation statements)
references
References 134 publications
1
255
1
7
Order By: Relevance
“…Another challenge that cells may frequently face in the environment is D-amino acids, which many bacteria release into the medium in considerable amounts after transition to the stationary growth phase (40). D-Amino acids were shown to significantly affect peptidoglycan biosynthesis, either by replacing the terminal D-alanine residues of the peptide side chains and thus affecting their recognition by peptidoglycan-modifying enzymes or by directly blocking the substrate-binding site of transpeptidases (41,42). We observed that the C. crescentus wild type was resistant to elevated concentrations of D-alanine.…”
Section: Resultsmentioning
confidence: 99%
“…Another challenge that cells may frequently face in the environment is D-amino acids, which many bacteria release into the medium in considerable amounts after transition to the stationary growth phase (40). D-Amino acids were shown to significantly affect peptidoglycan biosynthesis, either by replacing the terminal D-alanine residues of the peptide side chains and thus affecting their recognition by peptidoglycan-modifying enzymes or by directly blocking the substrate-binding site of transpeptidases (41,42). We observed that the C. crescentus wild type was resistant to elevated concentrations of D-alanine.…”
Section: Resultsmentioning
confidence: 99%
“…D-Amino acids incorporate into the peptide cross bridge of the peptidoglycan component of the cell wall (5,6,11). It was previously shown that D-tyrosine, D-leucine, D-tryptophan, and D-methionine were active in inhibiting biofilm formation by B. subtilis, whereas D isomers of other amino acids, such as D-phenylalanine, were inert in inhibiting biofilm formation (10).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that D-amino acids such as D-Ala and D-Glu are structural components of bacterial peptidoglycan, which make the bacterial cell wall resistant to proteases (10). D-amino acid is also an important structural and functional component of diverse bioactive peptides that act as analgesics, antimicrobials, and bactericidal agents among many others (9). More recently, research has begun to reveal important physiological roles of D-amino acids in bacteria and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…D-amino acids also play important structural and physiological roles in diverse life systems. In bacteria, D-amino acids confer cell-wall protease resistance and regulate cell-wall remodeling (9)(10)(11). D-amino acids were also found to be involved in signaling mechanisms in animal nervous systems and plant pollination (12,13).…”
mentioning
confidence: 99%